EVALUASI SISTEM DRAINASE DI UNIVERSITAS KEBANGSAAN REPUBLIK INDONESIA - Imanda, Devina; Muchamad, Arief Nur; Novia, Fanny (ENVIROSAN : Jurnal Teknik Lingkungan, 2024)
The drainage system is an important component in an area. Water discharge from the hydrological cycle or from activities in the area will be channeled into the drainage system that has been built. There will be no flooding or disruption to area activities if the drainage system is built properly. This research was conducted to determine flood discharge and flow discharge in drainage channels and then determine the factors that cause inundation at certain locations at University Kebangsaan Republik Indonesia. Quantitative methods were used in this research with hydrological mapping and also literature studies taken from several books, journals and other supporting sources related to this research, making it easier to collect data, analyze data, process data and prepare reports.. The results of the planned flood discharge compared to the existing channel discharge with a Daily Return Period (PUH) of 5 years showed that the flood discharge (Q flood) = 0.7812 m3/s and the existing channel discharge (Q existing) = 10.0091 m3/s, then the existing and planned channels are still feasible and can be used for the next 5 years. Factors that cause flooding in several locations at the Universitas Kebangsaan Republik Indonesia are uneven land elevations, roads with holes and rainwater flow that does not enter drainage channels. Keywords: Drainage system, Flood Discharge, Existing Discharge.